2019
DOI: 10.6061/clinics/2019/e1399
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution computed tomography findings in young infants with cystic fibrosis detected by newborn screening

Abstract: OBJECTIVE:High-resolution computed tomography (HRCT) allows the early detection of pathological changes in the lung structure, and reproducible scoring systems can be used to quantify chest computed tomography (CT) findings in patients with cystic fibrosis (CF). The aim of the study was to describe early HRCT findings according to a validated scoring system in infants with CF diagnosed by newborn screening (NBS).METHODS:This cross-sectional study included infants with CF diagnosed by NBS who were born between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…According to the latest National Institute for Health and Care Excellence (NICE) guideline for CF diagnosis and management, a routine review on the clinical condition of children with clinical evidence of CF-related lung disease, including taking respiratory secretion samples and pulmonary function tests (PFTs), should be performed at least every 8 weeks and chest imagings are recommended to be performed on an annual basis ( 11 ). However, using respiratory cultures for direct clinical management of CF is still challenging and studies have reported conflicting results regarding the association between the microbiological yield and structural and functional lung changes in different age groups and study settings ( 12 15 ). The aim of our study was to assess the potential association between bacterial colonization detected by sputum cultures and pulmonary structural and functional changes in Iranian children with CF.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest National Institute for Health and Care Excellence (NICE) guideline for CF diagnosis and management, a routine review on the clinical condition of children with clinical evidence of CF-related lung disease, including taking respiratory secretion samples and pulmonary function tests (PFTs), should be performed at least every 8 weeks and chest imagings are recommended to be performed on an annual basis ( 11 ). However, using respiratory cultures for direct clinical management of CF is still challenging and studies have reported conflicting results regarding the association between the microbiological yield and structural and functional lung changes in different age groups and study settings ( 12 15 ). The aim of our study was to assess the potential association between bacterial colonization detected by sputum cultures and pulmonary structural and functional changes in Iranian children with CF.…”
Section: Introductionmentioning
confidence: 99%